Fever response induced by intravenous and intracerebrovascular injection of pyrogen in thyroidectomised and protein-calorie malnourished rabbits - Macari, Marcos [UNESP]; Pela, I. R. [UNESP]; Silva, C. A A [UNESP]; Viana, R. S. [UNESP] (Springer Nature, 1990)
The development of a fever in response to intravenous (IV, 1.5 μg/kg body mass) and intracerebroventricular (ICV, 1.5 μg/animal) injections of Escherichia coli lipopolysaccharide (LPS) was studied in control, thyroidectomised and protein-calorie malnourished rabbits (New Zealand Whites, n = 55). ICV injection of LPS is control rabbits produced a fever response, the characteristics of which differed from those obtained after IV pyrogen injection. Thyroid deficiency caused an attenuated fever response, irrespective of whether LPS had been administered by IV or ICV injection. Protein-calorie malnourished rabbits showed a smaller fever response after IV or ICV pyrogen injections. Malnourished rabbits, refed over a period of 15 days, showed a typical biphasic fever response, but with lower magnitude than controls. The results of these experiments suggest that ICV injection of LPS is not an appropriate model for the study of fever mechanisms in disease states, and that the attenuated fever response observed in protein-calorie malnourished rabbits may be related, at least in part, to a decreased ability to produce the endogenous pyrogen interleukin-1.
Keywords: Fever; Interleukin-1; Malnutrition; Protein-calorie; Rabbit; Thyroid deficiency; animal cell; animal experiment; caloric restriction; fever; intracerebroventricular drug administration; intravenous drug administration; male; malnutrition; nonhuman; priority journal; protein deficiency; rabbit; thermoregulation; thyroidectomy; Animal; Escherichia coli; Injections, Intravenous; Injections, Intraventricular; Lipopolysaccharides; Male; Protein-Energy Malnutrition; Pyrogens; Rabbits; Support, Non-U.S. Gov't; Thyroidectomy